Pengaruh Stigmatisasi Pada Penyalah Guna Narkotika Berdasarkan Gender Terhadap Kecenderungan Penggunaan Berulang di Balai Rehabilitasi BNN - Putri, Agrippina Decila; Puspitasari, Puspitasari,; Utami, Diah Setia (Jurnal Kajian Stratejik Ketahanan Nasional, 2021)
Stigmatization of narcotics abusers is strongly felt in the community. The stigma that is formed in society can have implications for the internalization of self-stigma so that it affects the tendency of repeated use. This thesis aims to identify the public stigma and self-stigma that is formed on narcotics abusers based on gender on the influence of the tendency of repeated use at the BNN Rehabilitation Center which consists of the Lido BNN Rehabilitation Center, the Baddoka Makassar BNN Rehabilitation Center and the Tanah Merah Samarinda Rehabilitation Center. . This thesis research uses a mixed method. The research sample amounted to 168 male respondents and 20 female respondents. Quantitative data were analyzed using SPSS 23. The result of this study is that stigmatization of narcotics abusers can affect the tendency of repeated use. In male gender, public stigma is greater than public stigma for women and self-stigma for men is smaller than self-stigma for women. So that there is an influence between stigmatization of narcotics abusers at the BNN Rehabilitation Center. Keywords: Stigma, Public Stigma, Self Stigma, Gender, Repeated Use, Narcotics, Rehabilitation